Refugee status as a productive tension. (3rd April 2015) - Novak, Paolo
Abstract : Who is an Afghan refugee in Pakistan? The paper delves into this question through a detailed discussion of the concrete mechanisms that contextually define who an Afghan refugee in Pakistan is. Drawing on an understanding of law as generatively irresolute, the paper is concerned with how the conditions of refugee status come into being, are maintained and transformed. The study advances a conceptualisation of refugee status as a productive tension between the content of law and its 'excesses', ie the multi-scalar meanings and practices that are an integral aspect of refugee status recognition, but that cannot be fully absorbed or contained by law. It highlights contributions that such conceptualisation can offer to refugee legal scholarship and its exclusive concern with state-centred understandings of the refugee. It intervenes in Foucaultian legal scholarship debates on the relation between law and disciplinary modalities of power, insisting on a theorisation of law that is firmly grounded in context. The conceptualisation of refugee status as a productive tension proposed here can contribute to a better understanding of the fluid and dispersed ways through which law manifests itself across society and the increasingly complex role assumed by law in modern society.